J. P. H. Hansen, J. Meldgaard og J. Nordqvist (red,): Qilakitsoq. De grønlandske mumier fra 1400-tallet. (Grønlands Landsmuseum. Christian Ejlers' Forlag, 1985). 216 s. ill. - Kjær Sørensen, Axel (Historie/Jyske Samlinger, 1987)
-